Side stream control in semicontinuous distillation. (2nd November 2018) - Madabhushi, Pranav Bhaswanth; Adams, Thomas A.
Highlights: The first comprehensive study on changing the side stream control and its effect on the cycle time and separating cost of the semicontinuous distillation process. Demonstrates the importance of the nature of side stream flow rate function in semicontinuous distillation. A significant reduction in cycle time and separating cost (performance measures) is reported by using a new feed forward model for side stream flow rate control and demonstrated the generalizability of the model to n-component semicontinuous distillation with similar improvements to the performance. Used dynamic optimization with periodic constraints to find a side stream flow rate trajectory that minimizes the separating cost. Abstract: The idea to reduce cycle time ( T ), by controlling the side stream flow rate using a feedforward control model – the ideal side draw recovery arrangement (ISR) – was standard in most semicontinuous distillation studies. However, its effect particularly on ' T ' and more broadly on the system dynamics was not clearly understood. In the current study, we compare the performance of using a modified form of ISR model with the status quo based on the criteria T and separating cost (SC) on different case studies. Results show that the modified control model performed better with a 10-20% reduction in SC while maintaining product purities. Furthermore, the side stream flow rate trajectory that minimizes SC was found by using dynamic optimization and it did not differ a lot from the trajectory generated by the modified control model. The improvement in SC was at most 2%.